Systematic Literature Review Profil Gangguan Suara Post-Thyroidectomy - Hikmatun Sadiah sadiah; Najma Alythea (Jurnal Terapi Wicara, 2025)
Background: Thyroidectomy is a common surgical procedure for the management of thyroid disorders. However, postoperative voice changes remain a significant concern, potentially resulting from recurrent laryngeal nerve (RLN) injury, external branch of the superior laryngeal nerve (EBSLN) damage, or functional dysphonia without nerve paralysis. These alterations can substantially affect communication ability and quality of life, particularly among professional voice users. Objective: This study aims to systematically review the profile, mechanisms, incidence, and prognosis of voice disorders following thyroidectomy procedures. Methods: A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. Relevant articles were identified through PubMed, Scopus, and ScienceDirect databases using predefined inclusion and exclusion criteria. Eligible studies involved adult patients (≥18 years) undergoing total, subtotal, or hemithyroidectomy with reported voice-related outcomes. Data extraction focused on nerve injury types, clinical manifestations, diagnostic methods, and therapeutic approaches. Results: Voice disorders were reported in 1–10% of RLN palsy cases, 2–30% of EBSLN injuries, and up to 50% of early postoperative functional dysphonia. Most cases were transient and improved within 3–6 months, particularly with structured voice therapy. Early diagnosis and multidisciplinary rehabilitation contributed to better phonatory recovery. Conclusion: Post-thyroidectomy voice disorders represent multifactorial complications requiring early detection, intraoperative nerve monitoring, and individualized voice rehabilitation to optimize long-term vocal outcomes and patient quality of life